Maternal Knowledge and Behavior as Prevention of Anemia in Pregnancy: A Health Facility-Based Cross-Sectional Study Design - Futihandayani, Annisa; Siagian, Iswadi; Febriani, Febriani (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: The incidence of Maternal Anemia in Indonesia (48.9%), which exceeds the WHO standard of >40%, signifies a severe public health concern that requires immediate attention and intervention. Consuming iron-rich meals and supplements with regular antenatal care visits in early pregnancy reduces maternal anemia rate. Our study aims to determine the relationship between the level of knowledge and behavior during pregnancy and the incidence of anemia. Method: A descriptive-analytic cross-sectional study was conducted at Sukaindah Primary Health Care Center in September and October 2023. Pregnant women who attended Antenatal Care (ANC) underwent hemoglobin tests. Seventy-eight respondents were selected using consecutive sampling. The knowledge and behaviors of anemic pregnant women were compared to those without anemia. The validated-modified questionnaire consists of twenty questions to measure knowledge and eleven questions to assess behavior. Result: All respondents were dominated by poor knowledge (83%) and fair preventive behavior (61.5%) about anemia in pregnancy. Although the level of knowledge was not significantly associated with the incidence of anemia (p-value: 0.277), women who were found in the level of good (33%) and fair knowledge (55%) showed good behavior (p-value = 0.007) for its prevention. There was a statistically significant association between behavior during pregnancy and the incidence of anemia (p-value = 0.025). Iron supplementation emerged as a critical factor in preventing anemia in pregnancy. (mean: 1.38). Conclusion: Knowledge and behavior are the most important aspects of anemia prevention strategies. Good behavior is based on adequate knowledge, as poor knowledge triggers bad behavior. Behavioral factors play a statistical role in preventing anemia, but knowledge does not show a significant relationship in pregnant women with anemia.Pengetahuan dan Perilaku Pencegahan terhadap Kejadian Anemia Ibu Hamil di Puskesmas SukaindahAbstrak Tujuan: Tingkat kejadian anemia kehamilan di Indonesia sebesar 48.9%. Hal ini merupakan suatu severe public health problem berdasarkan WHO (> 40%). Pengaturan pola makan tinggi zat besi, teratur meminum tablet zat besi, dan rutin melakukan ANC pada kehamilan trimester awal ialah faktor penting mengurangi kejadian anemia pada ibu hamil. Perilaku atau tindakan seseorang dibentuk berdasarkan pengetahuan (knowlegde) atau kognitif. Studi ini bertujuan mengetahui hubungan tingkat pengetahuan dan perilaku selama hamil terhadap kejadian anemia. Metode: Studi deskriptif analitik dengan metode cross sectional ini berpopulasi pada ibu hamil yang melakukan pemeriksaan ANC di Puskesmas Sukaindah selama bulan September dan Oktober 2023 dan melakukan pemeriksaan hemoglobin. Pemilihan sampel secara consecutive sampling didapatkan 78 responden Ibu hamil. Modifikasi kuesioner yang sudah tervalidasi terdiri dari dua puluh pertanyaan untuk pengetahuan dan sebelas pertanyaan untuk perilaku. Hasil: Seluruh responden didominasi dengan pengetahuan buruk (83%) dan perilaku yang cukup (61.5%). Studi menunjukkan terdapat hubungan antara perilaku selama hamil dan kejadian anemia (p value = 0.025), namun tingkat pengetahuan tidak berhubungan secara signifikan (p value = 0.277). Ibu dengan pengetahuan yang baik (33%) dan cukup (55%) berhubungan secara signifikan (p value= 007) menghasilkan perilaku pencegahan yang baik. Konsumsi rutin tablet tambah darah berperan sebagai pencegahan kejadian anemia ibu hamil (mean: 1.38) Kesimpulan: Perilaku yang baik didasari oleh pengetahuan yang cukup, begitu juga dengan perilaku buruk dipicu oleh kurangnya pengetahuan. Faktor perilaku berperan secara statistik mencegah kejadian anemia, namun pengetahuan tidak menunjukkan hubungan bermakna pada ibu hamil dengan anemia.Kata kunci: Anemia, Kehamilan, Pengetahuan, Perilaku.